Ambient electromagnetic energy harvesting system for on‐body sensors. Issue 22 (1st October 2016) - Shaker, G.; Chen, R.; Milligan, B.; Qu, T.
Abstract : An ambient electromagnetic energy harvesting system for on‐body sensors is presented. Specifically, a smart contact lens that monitors the glucose level in the tear fluid of a user is demonstrated. The energy harvesting system rectifies a portion of a cell phone/smartphone‐emitted uplink signal into DC power for the operations of on‐lens sensors and components. An actual cow eye is used to assist in various measurements of the proposed energy harvester. Ultimately, a power of 1 mW at about 1 V is harvested and delivered to a resistive load of 2 KΩ when a cell phone is held in a typical reading position. This harvested power level is more than adequate to enable numerous possible on‐body sensors.